A Doubly Alkynylpyrene‐Threaded [4]Rotaxane That Exhibits Strong Circularly Polarized Luminescence from the Spatially Restricted Excimer1. (27th October 2014) - Inouye, Masahiko; Hayashi, Koichiro; Yonenaga, Yuki; Itou, Tatsuya; Fujimoto, Kazuhisa; Uchida, Taka‐aki; Iwamura, Munetaka; Nozaki, Koichi
Abstract The Sonogashira coupling of γ‐CD‐encapsulated alkynylpyrenes with terphenyl‐type stopper molecules gave a doubly alkynylpyrene‐threaded [4]rotaxane. The rotaxane showed only excimer emission, with a high fluorescence quantum yield of Φf=0.37, arising from the spatially restricted excimer within the cavity of the γ‐CD. The excimer emission suffered little from self‐quenching up to a concentration of 1.5×10−5 M and was circularly polarized with a high glum value of −1.5×10−2. The strong circularly polarized luminescence may result from the two stacked pyrenes existing in the rotaxane in an asymmetrically twisted manner.